Childhood reproductive hormone levels after pediatric hematopoietic stem cell transplantation in relation to adult testicular function. Issue 5 (September 2021) - Mathiesen, Sidsel; Sørensen, Kaspar; Ifversen, Marianne; Hagen, Casper P.; Holm Petersen, Jørgen; Juul, Anders; Müller, Klaus
Abstract : Objectives: Longitudinal assessment of testicular function after pediatric hematopoietic stem cell transplantation (HSCT) is needed to guide clinical follow-up. We investigated dynamics in male reproductive hormones after pediatric HSCT, focusing on pubertal timing and associations with testosterone deficiency and azoospermia in adulthood. Methods: This retrospective, longitudinal study included 39 survivors median 19 years after pediatric HSCT. Serum concentrations of LH, testosterone, FSH, and inhibin B from time of HSCT, during puberty, and into adulthood were analyzed. Pubertal timing (rise in LH and testosterone) was compared to a reference cohort of 112 healthy boys. Associations between reproductive hormone levels during puberty and adult testicular function (including semen quality) were investigated. Results: Pubertal induction with testosterone was needed in 6/26 patients who were prepubertal at HSCT. In the remaining patients, pubertal timing was comparable to the reference cohort. However, 9/33 patients (without pubertal induction) developed testosterone deficiency in early adulthood, which was associated with higher LH levels from age 14–16 years. Azoospermia in adulthood was found in 18/26 patients without testosterone substitution. Higher FSH and lower inhibin B levels from mid-pubertal age were associated with azoospermia in adulthood, in patients being prepubertal at HSCT. Conclusion: Our results indicate a substantial risk of deterioration in testicular function after pediatric HSCT, despite normal pubertal timing. Although reproductive hormone levels from mid-puberty indicated adult testicular function, prolonged follow-up into adulthood is needed in these patients, including clinical examination, reproductive hormone analysis, and semen sample for patients interested in their fertility potential.